Understanding The Impact Of Sustainable Marketing Influences Towards Malaysia’s Gen Z’s Green Consumption Intentions (Journal of Namibian Studies : History Politics Culture, 2023)
This study addresses a research gap by investigating the impact of sustainable advertising on consumption intentions among Malaysia's Generation Z (Gen Z), particularly those with limited sustainable consumption experience. Using a quantitative approach, 160 Gen Z respondents in Malaysia are involved. Alongside sustainable advertising, the study introduces variables like environmental distresses, perceived control, subjective norms, and cost, aiming to comprehend factors influencing sustainable consumption intentions. Primary data focuses on participants' perceptions of sustainable marketing's impact, environmental information, issues, and eco-friendly consumption intentions. The study emphasizes sustainable advertising's role in shaping green consumption intentions among Malaysia's Gen Z, highlighting the effectiveness of sustainable marketing in promoting environmentally conscious behavior. It identifies pivotal factors influencing Gen Z's inclination towards sustainable consumption practices. These insights recommend educational initiatives for environmental awareness and collaboration with businesses for sustainable consumption guidelines. Valuable for marketers, the study informs impactful strategies resonating with Gen Z and fostering sustainable consumption. By revealing the link between sustainable advertising and consumption intentions, the research advances informed environmental consciousness within this demographic.